Structural elucidation and estimation of the acute toxicity of the major UV–visible photoproduct of fludioxonil – detection in both skin and flesh samples of grape. (20th May 2015) - Lassalle, Yannick; Nicol, Édith; Genty, Christophe; Bourcier, Sophie; Bouchonnet, Stéphane
<x xml:space="preserve">Abstract</x> Ultraviolet (UV)–visible irradiation of fludioxonil was investigated with two photoreactors using either a mercury or xenon vapor lamp. In both cases, it led to the formation of only one photoproduct in significant amount: 2‐(2, 2‐difluorobenzo[d][1, 3]dioxol‐4‐yl)‐2‐(nitrosomethylene)‐4‐oxobutanenitrile, which has been characterized using Liquid Chromatography ‐ High Resolution ‐ Tandem Mass Spectrometry (LC‐HR‐MS/MS) coupling. A photolysis pathway has been proposed to rationalize its formation in degassed water. In vitro bioassays on Vibrio fischeri bacteria showed that UV–vis irradiation of an aqueous solution of fludioxonil significantly increases its toxicity. Because no other by‐product was detected in significant amount, the photoproduct mentioned above may be considered mainly responsible for this increase in toxicity. Grape berries treated with a 50 ppm aqueous solution of fludioxonil were submitted to UV–visible irradiation under laboratory conditions. The fungicide and photoproduct were detected in both skin and flesh of berries, even after they have been rinsed with water. The ability of the photoproduct to pass through the fruit skin is comparable with that of fludioxonil. These results are of concern for consumers because they mean that water tap rinsing does not lead to efficient removing of both compounds. Copyright © 2015 John Wiley & Sons, Ltd.